Effect of Production Processes on the Quality and Consumer Acceptability of Dried Bamboo Shoot - Kulvadee Trongpanich; Chidchom Hiraga; Urai Paowsungthong; Sompoch Yai-em (Agriculture and Natural Resources, 1993)
With the study on the process of dried bamboo shoot, it was found that blanching for 10 mins. and then soaking in 1.0% sodium metabisulfite prior drying maintained the better quality and highest acceptance of dried bamboo shoot after 6 month storage when compare to the non - pretreatment and treatment with soaking in 1% sodium metabisulfite prior drying. Conventional dryer provided faster drying rate than dehumidified dryer thus resulting in better quality dried product. Samples with non-treatment prior drying demonstrated higher drying and water - absorbing rates than those with pretreatment prior drying. Browning of dried products was increased with the increasing of storage time, as the L*, a*, and h values of the products from the color measurement were change gradually. The using of 1 % sodium metabisulfite solution can only retard the browning reaction of the product within 3 storage months.